Structured Oral Examinations in Internal Medicine - Case E - Hani Almoallim; Ali Alkatheeri; Alaa Monjed; Fozya Basheer; Abdullah Tawakol; Ahmad Imam; Abdulsalam Noorwali; Kamran Hameed (Association of American Medical Colleges, 2009)
Abstract This resource is one component of the nine-part Structured Oral Examinations in Internal Medicine series. In this case (Case E: Community-Acquired Pneumonia and Empyema and Diabetic Ketoacidosis [DKA]), a 60-year-old female diabetic patient complains of fever, productive cough for a day, and left-sided chest pain for 2 days. She is febrile and in respiratory distress with signs of consolidation and pleural effusion. She has all signs of empyema from pleural fluid analysis (pH= 7, Gram + cocci and pus) as well as high anion gap metabolic acidosis. She also has DKA as an additional cause of her acidosis. This approach of examination is very convenient to both students and examiners. It is structured and standardized. We were successfully able to avoid almost all disadvantages associated with long case format. The majority of our students enjoyed the exam from personal and written feedback we received after the exam.